ANALISIS VEGETASI DAN POLA SEBARAN SALINITAS DI EKOSISTEM MANGROVE PERCUT SEI TUAN KABUPATEN DELI SERDANG SUMATERA UTARA (Vegetation Analysis and Distribution Pattern of Salinity in Mangrove Ecosystem Percut Sei Tuan, Deli Serdang Regency, North Sumatera) - Muhammad Dafikri; Yunasfi Djayus; Zulham Apandy Harahap (AQUACOASTMARINE, 2016)
The decrease in mangrove area by 30-50% over the past half century provides functionally estimates that mangroves will be lost. Utilization of mangrove ecosystems increasingly large can cause loss of quality and physical function of mangroves, it is feared would disrupt ecological conditions and mangrove vegetation. This study aims to assess the condition of mangrove vegetation of density, frequency, dominance and diversity index mangrove species, to study the distribution pattern of salinity found in mangrove areas and examines the relationship between salinity of the mangrove species that dominate in the Mangrove Ecosystem Percut Sei Tuan Deli Serdang. The technique of taking a vegetation analysis performed using line transect sampling techniques or so-called squared (quadrat sampling technique) to determine the three stations that have each 3 plots and taking 30 points in all three observation stations salinity. This study using ArcGIS 9.3 software to create distribution maps of salinity. The results showed that the value of diversity index mangrove tree on the first station is 2.01, at the second station is 1.24 and at the third station is 1.64, so that the third grades of each stations in the criteria for being classified. Overview of the distribution of salinity produces a range of salinity fluctuated relatively small at between 23 - 24.5 ‰, 24.6 - 26.1 ‰, 26.2 - 27.6 ‰, 27.7 - 29.1 ‰ and 29.2 - 30.6 ‰ contained in all three observation stations.Keywords: Vegetation Analysis, Distribution Salinity, Mangrove Ecosystem